Relationship Between Humeral Retroversion and Career of Pitcher in Elementary and Junior High Schools. Issue 7 (21st July 2017) - Mihata, Teruhisa; Hirai, Hiromichi; HASEGAWA, AKIHIKO; Fukunishi, Kunimoto; Watanabe, Chisato; Fujisawa, Yukitaka; Kawakami, Takeshi; Yasui, Kenji; Itami, Yasuo; Ohue, Mutsumi; Neo, Masashi
Objectives: Repetitive throwing motion generates tremendous stress on the dominant shoulder in baseball players, resulting in osseous change in the shoulder joint, especially increased humeral retroversion. Here we hypothesized that the career of a pitcher in elementary and junior-high schools might increase humeral torsion on the dominant shoulder. The objective of this study was to assess the effect of baseball position in youth and adolescent athletes on humeral torsion. Methods: We studied 153 high school baseball players who began to play baseball in elementary school at the age of 8.1±1.6 years old. All subjects completed questionnaires about their baseball experience, throwing activity, and past injuries; they then were physically examined. We divided them into four groups according to their baseball positions in elementary and junior-high schools: 35 players were pitchers in both elementary and junior-high school (group 1), 32 players were pitchers in elementary school but fielders in junior-high school (group 2), 17 players were fielders in elementary school but pitchers in junior-high school (group 3), and 69 players were fielders in both elementary and junior-high school (group 4). Humeral torsion was assessed bilaterally by using ultrasound. Humeral torsion was defined as the angle between the long axis of the forearm and a line parallel to the trunk, when the line tangential to the bicipital groove was parallel to the horizontal baseline in supine position with the shoulder at 90º abduction, the elbow at 90º flexion, and the forearm in the neutral position. Results: Beginning age of baseball did not differ significantly among four groups. Among the 153 high school baseball players, 113 players (73.9%) had history of shoulder or elbow injuries. Humeral torsion was significantly greater (p<0.01) on the dominant shoulder than on the non-dominant shoulder in all groups. Humeral torsion on the dominant shoulder was significantly greater (p=0.03) in group 1 than in group 4 (mean difference, 7.1º). A logistic regression analysis showed that humeral torsion on the dominant shoulder was not a predictive factor for shoulder and elbow injuries (odds ratio, 0.99; 95% confidence interval, 0.96 - 1.02; p value, 0.70). Conclusion: In high school baseball players, humeral torsion was greater on the dominant shoulder than on the non-dominant shoulder. Players who played baseball as pitchers during both elementary and junior-high school had greater humeral torsion on the dominant side than did players who were fielders during both periods. Given that pitchers throws more frequently than do fielders, this study suggests that increased time pitching in youth and adolescent athletes increases the humeral torsion on the dominant shoulder. Increased humeral torsion on the dominant shoulder was not the predictive factor for shoulder and elbow injuries.